Analisis Penguatan Profil Pelajar Pancasila (P5) Untuk Menumbuhkan Jiwa Berwirausaha Di SDN 06 Tahunan - Hernum Satyanoviani Putri; Aniatus Sholikhah; Yunisatizzahroh Apriliani; Ramandhani Imelia Andriani; Dina Amalia (El-Miaz: Jurnal Pemikiran dan Pendidikan Dasar, 2023)
The Merdeka Curriculum has the advantage of focusing on essential material and developing student competencies in its phases. Strengthening the Pancasila Student Profile (P5) in the Merdeka Curriculum is implemented with the existence of a project with one of its themes namely entrepreneurship, with the aim of producing students who are ready for entrepreneurship. The purpose of this research is to find out the implementation of the application of P5 Entrepreneurship and to find out the formation of an Entrepreneurial spirit in students, especially class IV. This research is a qualitative research using descriptive qualitative data obtained based on the results of observations, interviews, questionnaires and documentation. The results of the research analysis obtained data that the implementation of the Strengthening Pancasila Student Profile Project (P5) had been carried out in accordance with the theme set by the government. Entrepreneurial spirit in students is formed through cultivating Pancasila student profiles in implementing projects by providing directions by teachers through providing materials for calculating selling prices. Student profile attitudes have been implemented in various learning activities including having faith and piety to God Almighty and having a noble character have been implemented with activities in the form of praying before carrying out project activities, being independent has been implemented with activities in the form of students being able to work on assignments given by the teacher, mutual cooperation cooperation in the form of students being able to help each other in making projects, global diversity which makes students have a small business from the results of making projects that can be sold, reasoning critically with activities in the form of students being given easy-to-understand examples from their teachers, being creative through activities in the form of students being able to create a unique craft or project. The implementation of entrepreneurial values ​​takes five main values, namely independence, creativity, responsibility, leadership, and interest in doing business. Through trading activities, students can be responsible for the work they do. So that P5's attitude has an impact and there is a connection with fostering an entrepreneurial spirit through the projects implemented.